Construction of the Meaning of Ayat Kursi: An Analysis of Al-Munir and At-Ta'wil An-Najmiyyah Interpretations Through Roland Barthes' Semiotics Approach : (Konstruksi Kandungan Makna Ayat Kursi: Telaah Tafsir Al-Munir Dan At-Ta’wil An-Najmiyyah Melalui Pendekatan Semiotika Roland Barthes) - Ali, Khansa Fathinatul Mawaddah; Masykuroh, Siti; Irawan, Yoga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
This study investigates how ideological meaning is constructed in Ayat Kursi through Roland Barthes’ semiotic approach, using Tafsir al-Munir and At-Ta’wil al-Najmiyyah as primary references, and how its transformation of meaning is manifested in Muslim religious practices. Ayat Kursi, widely recited and regarded as a means of protection, is often understood normatively, without further exploration of the sign systems embedded in its textual formulations. This research highlights that each expression in the verse holds broader and more complex meanings that go beyond literal interpretation. The findings show that, at the denotative level, Ayat Kursi describes Allah’s majesty and absolute power. At the connotative level, it conveys symbols of divine protection, spiritual strength, and Islamic identity. At the mythical level, the verse represents transcendent authority that governs human existence, portraying faith as a protective force through Allah’s unlimited power to repel danger, ward off evil, and bring peace. Furthermore, the study identifies three patterns in the transformation of Ayat Kursi’s meaning within religious practice: (1) a shift from spiritual-transcendental protection to its use as a magical-sympathetic object; (2) its role as a marker of identity and sacred space; and (3) a reduction of its rich, complex meanings into simplified, practical functions. By combining semiotic analysis with exegetical perspectives, this research contributes to deepening the study of Qur’anic interpretation and demonstrates the continued relevance of Ayat Kursi for contemporary Islamic discourse.